2020
DOI: 10.1002/jimd.12312
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype associated with variants in TANGO2 may be explained by a dual role of the protein in ER‐to‐Golgi transport and at the mitochondria

Abstract: TANGO2 variants result in a complex disease phenotype consisting of recurrent crisis-induced rhabdomyolysis, encephalopathy, seizures, lactic acidosis, hypoglycemia, and cardiac arrhythmias. Although first described in a fruit fly model as a protein necessary for some aspect of Golgi function and organization, its role in the cell at a fundamental level has not been addressed. Such studies are necessary to better counsel families regarding treatment options and nutrition management to mitigate the metabolic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 22 publications
7
63
0
Order By: Relevance
“…3B). Ntn superfamily members with structures similar to the RoseTTAFold model suggest that TANGO2 functions as an enzyme that might hydrolyze a carbon-nitrogen bond in a bile acid related membrane component (13). Based on the model, known mutations which cause disease (magenta spheres in Fig 3A) could act by hindering catalysis (R26K, R32Q, and L50P, near active site) or produce steric clashes (G154R) (14) in the hydrophobic core.…”
mentioning
confidence: 99%
“…3B). Ntn superfamily members with structures similar to the RoseTTAFold model suggest that TANGO2 functions as an enzyme that might hydrolyze a carbon-nitrogen bond in a bile acid related membrane component (13). Based on the model, known mutations which cause disease (magenta spheres in Fig 3A) could act by hindering catalysis (R26K, R32Q, and L50P, near active site) or produce steric clashes (G154R) (14) in the hydrophobic core.…”
mentioning
confidence: 99%
“…However, studies on patient fibroblasts lacking TANGO2 protein found no indication of Golgi-ER fusion or reduced Golgi volume 1 . Reports of the size of Golgi membranes in patient-derived fibroblasts have been inconsistent, with contradictory report of changes in Golgi organization or size between patients and controls 1,3,4,7 . However, additional studies have suggested a possible impairment in retrograde ER-Golgi trafficking 8 .…”
mentioning
confidence: 99%
“…However, additional studies have suggested a possible impairment in retrograde ER-Golgi trafficking 8 . Of particular interest is the finding that while ER-to-Golgi transport is significantly delayed in TANGO2 deficient patients, the production of TANGO2 protein in these patient cells can rescue the transport process 7 . Taken together, these findings suggest that TANGO2 does in fact play a significant role in ER-Golgi trafficking without a notable impact on Golgi morphology.…”
mentioning
confidence: 99%
“…The microtubule-associated protein futsch-like gene supports the relationship we have identified due to its role in cellulose synthesis. However, marker A5067 was located on the transport and Golgi organization in the 2 homologous gene, and although this gene has been reported to be involved in traffic between the endoplasmic reticulum and the Golgi apparatus [ 43 ], its function has not been clarified. In this study, it has been determined that this gene has a relationship with Verticillium wilt disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it has been determined that this gene has a relationship with Verticillium wilt disease. On the other hand, transport and Golgi organization in the 2 homologous gene have been reported to be associated with some diseases in humans and drosophila [ 43 ]. The A1772 marker was located on the LOC107951191 (protein networked 1D-like) gene and there is no information about the function of this gene.…”
Section: Discussionmentioning
confidence: 99%